Pengembangan Perangkat Pembelajaran Matematika Terintegrasi dengan Pengembangan Kecerdasan Emosional dan Spiritual - M Syawahid (Beta: Jurnal Tadris Matematika, 2013)
This study aims to develop a valid, practical, and effective mathematics learning kitsintegrated in the development of emotional and spiritual intelligence.The development of the learning kits in this study employed Model 4-D by Thiagarajan, Semmel & Semmel that had been modified. Through the development process, this study has produced: (1) mathematics learning kits integrated in the ESI development and (2) research instruments. the results of the study showed that the mathematics learning kits integrated in the ESI developmentmeets the validity, practicality, and effectiveness criteria. The validity criteria can be viewed from validity analysis of the kits integrated in the ESI development that is in the valid category, the practicality of the kits integrated in the ESI development can be viewed from the practically belong to teacher that is in the easy to use category and practically belong to students is positive. The effectiveness of the kitsis on the basis of: (1) the percentage of the attainment of the students’ learning mastery classically with the moderate and high mastery levels being 80% of 20 students sitting for the test; (2) the percentage of the students’ ESI with the good level, being 80%.